The Multimodal Treatment of Acromegaly: Current Status and Future Perspectives - Espinosa, Etual; Ramirez, Claudia; Mercado, Moises (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2014)
Acromegaly is a chronic systemic disorder caused by a GH-secreting pituitary adenoma. Active acromegaly results in a poor quality of life due to symptoms such as headache, fatigue, arthralgia, depression, sexual dysfunction and hyperhidrosis; an increased prevalence of co-morbidities like diabetes, hypertension as well as cancer risk and a reduced life expectancy. Appropriate, modern, multimodal treatment of acromegaly has led to a significant improvement in quality of life, an adequate control of co-morbidities and a drastic reduction in the mortality rates that used to prevail in the past. This multimodal strategy includes an adequate selection of patients who are likely to benefit from surgical treatment (which has to be performed by a skilled pituitary neurosurgeon), the use of pharmacological interventions such as somatostatin analogs and dopamine agonists, which target the pituitary adenoma; and pegvisomant, a GH mutant acting as a competitive antagonist of the GH receptor. Radiation therapy is an important tool, particularly in parts of the World where resources are limited. The ultimate outcome of the individual patient depends on the judicious use of all these treatment options, which are critically analyzed in this mini-review.
Keywords: octreotide